The Vamana Temple - Temples of India Project Team (Jio Institute, 2024)
The temple is dedicated to Vamana Vishnu and is the smallest temple in the Baroli group of temples. Situated next to the Mahishasuramardini Temple, the temple faces east and has a shallow antarala (vestibule) and a small garbhagriha (sanctum sanctorum) on plan.